(untitled) (Bangladesh Journal of Microbiology, 2019)
Food borne pathogenic enteric bacteria are of great concern for global public health. Among them, Escherichia coli and Enterobacter spp. are the most prevalent in the street food. In this study, 23 strains of such enteric bacteria were isolated from multiple food samples by conventional cultural technique. Isolated strains were characterized molecularly into different genotypes using RAPD, amplified ribosomal DNA restriction analysis, and partial sequencing of 16S rDNA. RAPD represents 10 different types of strains whereas ARDRA clusters them into two separate groups. 16 out of the 23 isolates were identified as E. coli and the rest were as Enterobacter spp. by biochemical tests and were further confirmed by partial 16S rDNA sequencing. Significant level of virulence traits including stx1, stx2 and escV genes were identified in E. coli strains. Also, most of the isolates were found resistant to azithromycin and amoxicillin. This study revealed the presence of various pathogenic enteric bacteria in various street foods with multidrug resistance. Therefore, this study suggests that people consuming such street foods are at major risk of food borne illness. Bangladesh J Microbiol, Volume 34 Number 2 December 2017, pp 67-72